2011
DOI: 10.1038/nrd3595
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology as a cornerstone of orphan drug development

Abstract: A recent US Food and Drug Administration (FDA) advisory committee meeting highlighted the potential of clinical pharmacology to overcome challenges in orphan drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…This proposal implies that much of the understanding of PKPD, including the characterization of resistance development, can indeed be gained from experimental systems. In addition, more efficient use of clinical pharmacology data can limit the number of trial subjects, as advocated in orphan drug development (Schmidt et al, 2008;Bashaw et al, 2011;Bassetti et al, 2011).…”
Section: F Drug Development Of Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…This proposal implies that much of the understanding of PKPD, including the characterization of resistance development, can indeed be gained from experimental systems. In addition, more efficient use of clinical pharmacology data can limit the number of trial subjects, as advocated in orphan drug development (Schmidt et al, 2008;Bashaw et al, 2011;Bassetti et al, 2011).…”
Section: F Drug Development Of Antibioticsmentioning
confidence: 99%
“…It has been suggested that antibiotic drug development should be based on development strategies similar to those for orphan drugs (Bashaw et al, 2011) where quantitative approaches have a key role in decision making during all phases of clinical development. Furthermore, with model-based analysis, the number of patients needed can be reduced substantially while preserving the statistical power of the study (Vong et al, 2012).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Considering the regulatory flexibility exercised by the FDA (and by similar agencies outside of the US) in regard to marketing approvals where orphan drugs are concerned (Bashaw et al 2011), approval of plant-derived GCD seems a low-hanging fruit. In fact, a similar breakthrough came very recently with the emergency approval of a plant-derived monoclonal antibody cocktail to save the lives of two gravely ill physicians who contracted Ebola virus while treating patients in Africa (Bishop 2015; McCarthy 2014; Qiu et al 2014; Rybicki 2014).…”
mentioning
confidence: 99%
“…Before resources are dedicated to rare diseases, well‐defined means to overcome the obstacles of drug development should be delineated. Some of these strategies applicable to orphan drug development have been proposed in recent publications . These include cross‐subsidies, risk sharing, multiple indications in development, quantitative and Bayesian adaptive analyses, flexible and evidence‐based designs, surrogate endpoint verification, formation of rare disease frameworks, up‐to‐date formulation technologies, and potentially the pay for performance, conditional approvals, and the use of consortium/multiarm studies involving several companies.…”
mentioning
confidence: 99%